A resource-based analysis of e-commerce in developing countries - Boateng, R.; Hinson, R.; Heeks, R.; Molla, A.; Mbarika, V. (18th European Conference on Information Systems, ECIS 2010, 2010)
Electronic Commerce is touted as a panacea for business growth and expansion in relation to both small and large firms irrespective of their geographical locations. Past research in the area shows that there is an acute lack of theoretical frameworks and empirical evidence to understand how developing country firms realise e-commerce benefits amidst their national constraints. This paper sets out to develop a theoretically abstracted but contextually grounded electronic commerce appropriation and use model for developing country contexts. We undertake a review of the ecommerce and strategy management literature in order to arrive at our conceptual model. We develop a resource - based view model of electronic commerce benefits that posits that developing country firms can orient resources towards the creation and sustenance of electronic commerce benefits. This conceptual framework provides good theoretical platform for empirically grounded research on electronic commerce in developing country contexts. We have opened a new stream of understanding in respect of developing country electronic commerce adoption.
Keywords: Adoption; Developing countries; Electronic commerce; Strategy